Islamic Headdress Influences How Emotion is Recognized from the Eyes - Kret, Mariska; De Gelder, Beatrice (Frontiers in Psychology, 2012)
Previous research has shown a negative bias in the perception of whole facial expressions from out-group members. Whether or not emotion recognition from the eyes is already sensitive to contextual information is presently a matter of debate. In three experiments we tested whether emotions can be recognized from the upper part of the face only when just the eyes are visible and whether this recognition is affected by context cues, such as various Islamic headdresses versus a cap or a scarf. Our results indicate that fear is still well recognized from a briefly flashed (100ms) image of the eyes in the context of a burqa leaving the eyes visible for less than 20%. Moreover, the type of headdress influences how emotions are recognized. In a group of participants from non-Islamic background, fear was recognized better from women wearing a niqāb than from women wearing a cap and a shawl, whereas the opposite pattern was observed for happy and sad expressions. Anxiety levels and/or explicit negative associations with the Islam as measured via questionnaires did not mediate the effects. Consistent with the face literature, we conclude that the recognition of emotions from the eyes is also influenced by context.